Corridors of Clarity: Four Principles to Overcome Uncertainty Paralysis in the Anthropocene. (28th October 2020) - Polasky, Stephen; Crépin, Anne-Sophie; Biggs, Reinette (Oonsie); Carpenter, Stephen R; Folke, Carl; Peterson, Garry; Scheffer, Marten; Barrett, Scott; Daily, Gretchen; Ehrlich, Paul; Howarth, Richard B; Hughes, Terry; et al.
Abstract: Global environmental change challenges humanity because of its broad scale, long-lasting, and potentially irreversible consequences. Key to an effective response is to use an appropriate scientific lens to peer through the mist of uncertainty that threatens timely and appropriate decisions surrounding these complex issues. Identifying such corridors of clarity could help understanding critical phenomena or causal pathways sufficiently well to justify taking policy action. To this end, we suggest four principles: Follow the strongest and most direct path between policy decisions on outcomes, focus on finding sufficient evidence for policy purpose, prioritize no-regrets policies by avoiding options with controversial, uncertain, or immeasurable benefits, aim for getting the big picture roughly right rather than focusing on details.